2017
DOI: 10.1142/s2010135x17500060
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced thermal and pyroelectric properties in 0–3 TGS:PVDF composites doped with graphene for infrared application

Abstract: Pyroelectric composites of triglycine sulfate (TGS)-polyvinylidene difluoride (PVDF) doped with graphene are studied. It is found that the graphene can effectively improve the polling efficiency and thermal property of the composites so that the infrared detective performance can be significantly improved. For example, by adding about 0.83 wt.% of graphene, the infrared detective property can be improved by more than 30%. It is also found that the size of the graphene plays a critical role on the property impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…Such composites combine the flexibility, light weight, and high dielectric strength of polymers with the large dielectric permittivity, and piezoelectric and pyroelectric coefficients of inorganic ferroelectrics. It is shown that the introduction of ferroelectric nanoparticles, such as BaTiO 3 , Pb(Zr,Ti)O 3 , or TGS, into polymers yields capacitors with significantly enhanced piezoelectric and pyroelectric coefficients, as well as stored energy density [20][21][22][23][24][25][26][27][28][29][30][31][32]. The morphology of the filler, its volume fraction, the surface properties of the filler, the properties of the polymer-filler interface, and the distribution of the filler in the polymer matrix play important roles in optimizing the energy storage properties.…”
Section: Introductionmentioning
confidence: 99%
“…Such composites combine the flexibility, light weight, and high dielectric strength of polymers with the large dielectric permittivity, and piezoelectric and pyroelectric coefficients of inorganic ferroelectrics. It is shown that the introduction of ferroelectric nanoparticles, such as BaTiO 3 , Pb(Zr,Ti)O 3 , or TGS, into polymers yields capacitors with significantly enhanced piezoelectric and pyroelectric coefficients, as well as stored energy density [20][21][22][23][24][25][26][27][28][29][30][31][32]. The morphology of the filler, its volume fraction, the surface properties of the filler, the properties of the polymer-filler interface, and the distribution of the filler in the polymer matrix play important roles in optimizing the energy storage properties.…”
Section: Introductionmentioning
confidence: 99%